2020
DOI: 10.1371/journal.pone.0229026
|View full text |Cite
|
Sign up to set email alerts
|

Species and drug susceptibility profiles of staphylococci isolated from healthy children in Eastern Uganda

Abstract: Staphylococci are a key component of the human microbiota, and they mainly colonize the skin and anterior nares. However, they can cause infection in hospitalized patients and healthy individuals in the community. Although majority of the Staphylococcus aureus strains are coagulase-positive, some do not produce coagulase, and the isolation of coagulase-positive non-S. aureus isolates in humans is increasingly being reported. Therefore, sound knowledge of the species and characteristics of staphylococci in a gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…groin (95%, n = 9), axial (100%, n =1) and nasal cavity (1-%, n = 2) of hospitalized patients, some of the these isolates were resistant to about seven or eight antimicrobial classes, this is alarming given the possibility that these patients may act as a source of infection to health care personnel or source of contamination of hospital environment with these multiple resistant strains. The carriage of drug resistant Staphylococcus haemolyticus in the nares and skin of healthy as well as hospitalized individuals has been reported 24 .…”
Section: Resultsmentioning
confidence: 99%
“…groin (95%, n = 9), axial (100%, n =1) and nasal cavity (1-%, n = 2) of hospitalized patients, some of the these isolates were resistant to about seven or eight antimicrobial classes, this is alarming given the possibility that these patients may act as a source of infection to health care personnel or source of contamination of hospital environment with these multiple resistant strains. The carriage of drug resistant Staphylococcus haemolyticus in the nares and skin of healthy as well as hospitalized individuals has been reported 24 .…”
Section: Resultsmentioning
confidence: 99%
“…5% (2/41) were resistant to antibiotics belonging to six different classes, and thus considered pan resistant. These levels of resistance and MDR are not unexpected; for example, Seni and colleagues [9] reported 21% of Gram-positive isolates from surgical site wounds of patients in Mulago Hospital, Kampala (Uganda) were MDR, whereas Kateete and colleagues [34] observed 31% of S. aureus isolates recovered from nasopharyx of children in rural Eastern Uganda were MDR. A study of post-operative sepsis cases in rural Eastern Uganda [35] reported 14% S. aureus isolates to be resistant to five different classes of antibiotics and 3% resistant to six different classes [35].…”
Section: Resultsmentioning
confidence: 99%
“…S. chromogenes is a major cause of mastitis and subclinical mastitis in animals as seen in this review ( 21 , 56 , 57 , 66 , 75 , 76 , 84 , 90 , 106 ). However, no S. chromogenes infections were recorded in Botswana, Algeria, Ethiopia, Libya and Tanzania ( 42 , 46 , 58 – 62 , 64 , 70 , 73 , 87 , 93 , 120 ). The strain distribution could not be described due to the insufficient published data, but we were able to describe epidemiology of SOSA in terms of species distribution.…”
Section: Discussionmentioning
confidence: 99%